Home treatment for acute psychiatric illness. Issue 6759 (3rd November 1990) - Dean, C; Gadd, E M
Abstract : OBJECTIVE–To determine the factors influencing the successful outcome of community treatment for severe acute psychiatric illnesses that are traditionally treated in hospital. DESIGN–All patients from a single electoral ward who were either admitted to hospital or treated at home over a two year period (1 October 1987 to 30 September 1989) were included in the study and their case notes audited. The second year of the study is reported. SETTING–Electoral ward of Sparkbrook, Birmingham. SUBJECTS–99 Patients aged 16-65 with severe acute psychiatric illness. RESULTS–65 Patients were managed by home treatment alone; 34 required admission to hospital. The location of treatment was significantly (all p less than 0.05) influenced by social characteristics of the patients (marital state, age (in men), ethnicity, and living alone) and by characteristics of the referral (occurring out of hours; assessment taking place at hospital or police station). DSM-III-R diagnosis was more weakly associated with outcome. Violence during the episode was significantly related to admission, although deliberate self harm was not. CONCLUSIONS–Home treatment is feasible for most patients with acute psychiatric illness. A 24 hour on call assessment service increases the likelihood of success because admission is determined more strongly by social characteristics of the patient and the referral than by illness factors. Admission will still be required for some patients. A locally based mental health resource centre, a 24 hour on call service, an open referral system, and an active follow up policy increase the effectiveness of a home treatment service.